2013
DOI: 10.1016/s1734-1140(13)71527-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines, prostaglandins and nitric oxide in the regulation of stress-response systems

Abstract: Hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis is accepted as one of the fundamental biological mechanisms that underlie major depression. This hyperactivity is caused by diminished feedback inhibition of glucocorticoid (GC)-induced reduction of HPA axis signaling and increased corticotrophin-releasing hormone (CRH) secretion from the hypothalamic paraventricular nucleus (PVN) and extra-hypothalamic neurons. During chronic stress-induced inhibition of systemic feedback, cytosolic glucocorticoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
121
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(129 citation statements)
references
References 34 publications
1
121
0
7
Order By: Relevance
“…3 Tümer and colleagues 14 reported on increased hypothalamic expression of oxidative stress and activation of the sympathoadrenal medulla at an acute time-point of 6 h following blastinduced neurotrauma (BINT) in rats. 13 This study demonstrated that exposure to blast was associated with increased biosynthesis of catecholamine in the brain and elevated levels of stress-related biomarkers in serum. To our knowledge, however, no animal studies have been conducted to investigate the long-term hypothalamus pathology and associated pituitary dysfunction resulting from BINT.…”
mentioning
confidence: 78%
“…3 Tümer and colleagues 14 reported on increased hypothalamic expression of oxidative stress and activation of the sympathoadrenal medulla at an acute time-point of 6 h following blastinduced neurotrauma (BINT) in rats. 13 This study demonstrated that exposure to blast was associated with increased biosynthesis of catecholamine in the brain and elevated levels of stress-related biomarkers in serum. To our knowledge, however, no animal studies have been conducted to investigate the long-term hypothalamus pathology and associated pituitary dysfunction resulting from BINT.…”
mentioning
confidence: 78%
“…The cellular signalling molecule nitric oxide (NO), which is involved in the control of steroidogenesis in vertebrates (Ducsay and Myers 2011), can be synthesised from nitrate and nitrite (Castiglione et al 2012;Lundberg et al 2008). Nitric oxide is implicated in the regulation of the stress response (Gądek-Michalska et al 2013) although its role is not well-defined and it may exert different effects at different loci within the stress axis (Gulati et al 2015;Mancuso et al 2010). Teleost fish may utilise NO as a modulator of endocrine activity (Lal and Dubey 2013), and at least two of three NO synthase (NOS) isoforms are present in fish (see references in Mueller and O'Brien 2011).…”
Section: Discussionmentioning
confidence: 99%
“…expressed by other neurons in the highly heterogeneous PVN (Bodnar and Klein 2004;Tortorella et al 2007;Biag et al 2012;Gadek-Michalska et al 2013) as well as several transmitters/modulators that reach the PVN via extrinsic inputs from ascending and descending arousal/sensory systems, such as the serotonin and noradrenaline monoamine systems (Myers et al 2017;Ulrich-Lai and Herman 2009;Fox and Lowry 2013;Flak et al 2014). Further characterisation of existing and newly identified regulatory inputs is of interest for biological and therapeutical reasons.…”
Section: Introductionmentioning
confidence: 99%